Destructuration of saturated natural loess: From experiments to constitutive modeling. (April 2021) - Fu, Yukai; Gao, Zhiwei; Hong, Yi; Li, Tonglu; Garg, Akhil
It has been well recognized that unsaturated natural loess shows significant volume contraction upon wetting due to its metastable internal structure. But the structural effect on stress–strain relationship of saturated natural (undisturbed) loess is much less explored. Few attempts have been made in proposing a constitutive model for saturated natural loess. This study presents both laboratory tests and constitutive modeling of a saturated natural loess, with special focus on the structural effect and evolution of structure damage during loading. Oedometer and drained triaxial compression tests have been carried out on undisturbed and remolded saturated loess samples. It is found that the natural soil structure has dramatic influence on mechanical behavior of loess, including the compressibility, dilatancy, and shear strength. Destructuration, which is the damage of soil structure with deformation, is observed in both oedometer and triaxial tests. A constitutive model is proposed for saturated loess based on the experimental observations. The model is established within the theoretical framework of subloading and superloading surface concepts. Destructuration of loess is assumed to be affected by both plastic volumetric and shear strain. A new method for determining the initial degree of structure is proposed. The model can reasonably predict the compression and shear behavior of both undisturbed and remolded saturated loess.